2020
DOI: 10.1002/hbm.25033
|View full text |Cite
|
Sign up to set email alerts
|

Mapping brain asymmetry in health and disease through the ENIGMA consortium

Abstract: Left-right asymmetry of the human brain is one of its cardinal features, and also a complex, multivariate trait. Decades of research have suggested that brain asymmetry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 132 publications
(139 citation statements)
references
References 138 publications
(162 reference statements)
7
127
4
1
Order By: Relevance
“…Thus, loss of thickness asymmetry may be more relevant for advanced cognitive decline -such as that associated with AD -but less sensitive to individual differences in cognitive decline trajectories across the healthy adult lifespan. Although we note that alternative tests such as cognitive speed measures may be better suited than task accuracy for assessing asymmetry-cognition relationships, our results suggest that asymmetry-change may be unlikely to be a sensitive marker for age-related decline at the individual level (similar conclusions have recently been drawn in relation to asymmetry in other contexts 68 ). This is also evidenced by the fact that our large longitudinal sample sizes were needed to expose small-to-medium effects that nevertheless translated to consistent gradual changes in asymmetry across adult lifespan samples.…”
Section: Discussionsupporting
confidence: 51%
“…Thus, loss of thickness asymmetry may be more relevant for advanced cognitive decline -such as that associated with AD -but less sensitive to individual differences in cognitive decline trajectories across the healthy adult lifespan. Although we note that alternative tests such as cognitive speed measures may be better suited than task accuracy for assessing asymmetry-cognition relationships, our results suggest that asymmetry-change may be unlikely to be a sensitive marker for age-related decline at the individual level (similar conclusions have recently been drawn in relation to asymmetry in other contexts 68 ). This is also evidenced by the fact that our large longitudinal sample sizes were needed to expose small-to-medium effects that nevertheless translated to consistent gradual changes in asymmetry across adult lifespan samples.…”
Section: Discussionsupporting
confidence: 51%
“…The Davi130 parcellation was realized by utilizing macroscopic gyral and sulcal features such as peaks, fundi, and bends to represent the chimpanzee brain in a reduced dimensional space based on macro-anatomical landmarks. Despite the evidence that true microanatomical borders between brain areas rarely coincide with macro-anatomical patterns (Amunts and Zilles 2015), macroscopic brain parcellations like Desikan-Killany human atlas (Desikan et al 2006) have successfully been utilized in many studies furthering our understanding of brain structure, function, and disease (Kong et al 2020;van den Heuvel et al 2020). The Davi130 parcellation of the chimpanzee brain serves two main purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Our approach is akin to studying seismic waves of earthquakes with different wave frequencies at the global tectonic scale, instead of focusing on a particular city. The ability to assess shape along a spectrum of spatial scales is important, since brain asymmetry is a multidimensional and multivariate phenotype (3,13,45).…”
Section: Identifiability Of Cortical Shape Asymmetry Is Maximal At Coarse Scalesmentioning
confidence: 99%
“…Similarly, some studies have found associations between cerebral asymmetry and handedness (8,14,33), with others reporting no such effect (10,11,28,32,(34)(35)(36). Some of these inconsistencies may arise from the disparate methodologies and the heterogeneous nature of the brain asymmetries across the population (7,10,(12)(13)(14)(15). There is often considerable individual variability around population means, with many people often showing little or even reversed asymmetries relative to the group average (3,12,16,37).…”
Section: Introductionmentioning
confidence: 99%